2007
DOI: 10.1111/j.1365-2141.2007.06698.x
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide‐induced myelosuppression is associated with renal dysfunction: adverse events evaluation of treatment‐naïve patients undergoing front‐line lenalidomide and dexamethasone therapy

Abstract: Summary Data on 72 patients receiving lenalidomide/dexamethasone for multiple myeloma (MM) was used to determine the factors that are associated with lenalidomide‐induced myelosuppression. Eight of 14 patients with grade ≥3 myelosuppression had baseline creatinine clearance (CrCl) ≤0·67 ml/s. Kaplan–Meier analysis by log‐rank test demonstrated a significant association (P < 0·0001) between renal insufficiency and time to myelosuppression (hazard ratio = 8·4; 95% confidence interval 2·9–24·7, P = 0·0001). There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 10 publications
4
45
0
Order By: Relevance
“…76 However, in this report, only five patients had a serum creatinine 42 mg per 100 ml. Another study investigating the combination of lenalidomide with clarithromycin and dexamethasone showed that patients with a baseline creatinine clearance o40 ml/min were 8.4 times more likely to require lenalidomide dose reduction due to grade 3 or grade 4 myelosuppression, 77,78 thus indicating the need for lenalidomide dose adjustments according to renal function. Recommendations for lenalidomide use in patients with renal impairment have been formulated on the basis of a pharmacokinetic study in 30 patients with various degrees of renal impairment.…”
Section: Lenalidomidementioning
confidence: 99%
“…76 However, in this report, only five patients had a serum creatinine 42 mg per 100 ml. Another study investigating the combination of lenalidomide with clarithromycin and dexamethasone showed that patients with a baseline creatinine clearance o40 ml/min were 8.4 times more likely to require lenalidomide dose reduction due to grade 3 or grade 4 myelosuppression, 77,78 thus indicating the need for lenalidomide dose adjustments according to renal function. Recommendations for lenalidomide use in patients with renal impairment have been formulated on the basis of a pharmacokinetic study in 30 patients with various degrees of renal impairment.…”
Section: Lenalidomidementioning
confidence: 99%
“…Lenalidomide needs to be used with caution in the setting of CKD, and dose reduction is mandatory, because the drug is renally cleared. Despite this information, myelosuppression and other adverse events are more common in this setting (76)(77)(78). Nonetheless, it is not directly nephrotoxic, and therefore, a low dose (e.g., 5-10 mg/d) can be used.…”
Section: Systemic Therapymentioning
confidence: 99%
“…Given that earlier trials of lenalidomide excluded patients with serum creatinine levels >221 mol/l (creatinine >2.5 mg/dl) [87], these results are useful, although it is important to note that certain toxicities associated with lenalidomide (especially myelosuppression) are more likely to occur if the drug is used in patients with RI [88][89][90]. Furthermore, there have been isolated reports of progressive azotemia occurring during lenalidomide therapy in patients with MM and RI, so it is important to closely monitor renal function when lenalidomide is administered in this setting [89].…”
Section: Lenalidomidementioning
confidence: 99%